Pharmacokinetics of (99m)Tc-HMPAO in isolated perfused rat lungs - Clough, Anne V. (J Appl Physiol (1985), 2019)
Lung uptake of technetium-labeled hexamethylpropyleneamine oxime (HMPAO) increases in rat models of human acute lung injury, consistent with increases in lung tissue glutathione (GSH). Since (99m)Tc-HMPAO uptake is the net result of multiple cellular and vascular processes, the objective was to develop an approach to investigate the pharmacokinetics of (99m)Tc-HMPAO uptake in isolated perfused rat lungs. Lungs of anesthetized rats were excised and connected to a ventilation-perfusion system. (99m)Tc-HMPAO (56 MBq) was injected into the pulmonary arterial cannula, a time sequence of images was acquired, and lung time-activity curves were constructed. Imaging was repeated with a range of pump flows and perfusate albumin concentrations and before and after depletion of GSH with diethyl maleate (DEM). A pharmacokinetic model of (99m)Tc-HMPAO pulmonary disposition was developed and used for quantitative interpretation of the time-activity curves. Experimental results reveal that (99m)Tc-HMPAO lung uptake, defined as the steady-state value of the (99m)Tc-HMPAO lung time-activity curve, was inversely related to pump flow. Also, (99m)Tc-HMPAO lung uptake decreased by ~65% after addition of DEM to the perfusate. Increased perfusate albumin concentration also resulted in decreased (99m)Tc-HMPAO lung uptake. Model simulations under in vivo flow conditions indicate that lung tissue GSH is the dominant factor in (99m)Tc-HMPAO retention in lung tissue. The approach allows for evaluation of the dominant factors that determine imaging biomarker uptake, separation of the contributions of pulmonary versus systemic processes, and application of this knowledge to in vivo studies. NEW & NOTEWORTHY We developed an approach for studying the pharmacokinetics of technetium-labeled hexamethylpropyleneamine oxime ((99m)Tc-HMPAO) in isolated perfused lungs. A distributed-in-space-and-time computational model was fit to data and used to investigate questions that cannot readily be addressed in vivo. Experimental and modeling results indicate that tissue GSH is the dominant factor in (99m)Tc-HMPAO retention in lung tissue. This modeling approach can be readily extended to investigate the lung pharmacokinetics of other biomarkers and models of lung injury and treatment thereof.